Status Gizi Calon Pengantin Wanita - Yuni Handayani; Ririn Handayani (Oksitosin : Jurnal Ilmiah Kebidanan, 2023)
The nutritional health status of the prospective bride is a description of the physical well-being of the prospective bride on the fulfillment of nutritional needs in the body. The nutrition of the bride-to-be can have an effect on reproductive health to prepare for reproduction from preconception, pregnancy, delivery and post-delivery. The purpose of this study was to describe the nutritional status of the prospective bride in the KUA Kaliwates Region. This research used descriptive method. The population in this study was 47 respondents, the sampling technique used total sampling. The results of the study were obtained from direct examination of respondents regarding the status of the prospective bride, for the examination including measurements of Height, Weight and LILA. The results showed that all respondents in the reproductive age vulnerable (100%), the nutritional status according to the LILA measurement, most (63.8%) of normal nutritional status, blood pressure examination of 25 people (53.2%) in the susceptible normal. Examination of Upper Arm Circumference in partly 39 people (83%) in a normal assessment, Glucose examination in partly a bride-to-be of 47 people (100%) in a normal assessment.